Brain Teasers : Fifth Grader’s Inferential Reading and Logical Thinking Development through TBL. (2021)
English Language Teaching in Colombia may have been lacking innovation and consistent plans of education and formation. Then, meaningful activities which may place knowledge in context are left aside. In the pursuit of tools that might contribute to the improvement of the situations described above, brain teasers appear as a means to boost mental agility and significant English learning as well. These teasers are actually problems or puzzles designed to be solved for amusement. This pedagogical proposal aims to develop mental flexibility in fifth graders beyond traditional linguistic skills. Reading comprehension is expected to be enhanced inductively while logical thinking remains as the main concern. The literature review is approached through investigations and articles based on English language learning in young learners. Indeed, this proposal seeks fifth grade students to develop both reading skills and logical thinking simultaneously through the task-based learning approach.